2016
DOI: 10.1111/codi.13339
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stoma reversal in rectal cancer patients who had an anterior resection between 2009 and 2012 in the English National Health Service

Abstract: Overall, two-thirds of ileostomies were reversed within 18 months. Reversal rates were linked to patient and cancer characteristics (age, sex, fitness and stage), mode of surgical access and socioeconomic deprivation. Observed lower reversal rates in patients from poorer backgrounds may indicate inequity in access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 18 publications
6
41
0
3
Order By: Relevance
“…Although defunctioning stomas are intended to be temporary at the time of surgery, up to 25% will become permanent (Kuryba et al ., ; Sier et al ., ). The ACPGBI National Bowel Cancer Audit of 4879 patients who had an ileostomy during anterior resection between 2009 and 2012 reported a reversal rate of 72.5% within 18 months (Kuryba et al ., ).…”
Section: Surgical Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Although defunctioning stomas are intended to be temporary at the time of surgery, up to 25% will become permanent (Kuryba et al ., ; Sier et al ., ). The ACPGBI National Bowel Cancer Audit of 4879 patients who had an ileostomy during anterior resection between 2009 and 2012 reported a reversal rate of 72.5% within 18 months (Kuryba et al ., ).…”
Section: Surgical Managementmentioning
confidence: 99%
“…Even though anterior resection may be feasible, other factors such as body habitus, pre-existing incontinence, need for preoperative therapy or co-morbidities may mean that a permanent stoma is a better option for some patients (How et al, 2012). Although defunctioning stomas are intended to be temporary at the time of surgery, up to 25% will become permanent (Kuryba et al, 2016;Sier et al, 2015). The ACPGBI National Bowel Cancer Audit of 4879 patients who had an ileostomy during anterior resection between 2009 and 2012 reported a reversal rate of 72.5% within 18 months (Kuryba et al, 2016).…”
Section: Rates Of Permanent Stoma Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neoadjuvant radiotherapy, age, tumour size and tumour distance from the anal verge have also been reported as predictors of APR [3][4][5][6][7][8]. In addition, comorbidities, surgical complications, anastomotic leakage and local recurrence are associated with the creation of a permanent stoma after SPS [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage is the best studied risk factor for non-reversal, but high age and advanced tumor stage is also described [6][7][8][9]. Studies from countries with a social structure similar to Sweden have indicated that socioeconomic factors may also affect stoma reversal rates [9][10][11]. Road distance between home and hospital has not been studied as a risk factor for non-reversal.…”
Section: Introductionmentioning
confidence: 99%